Effectiveness of the Manori Sapuka Community-Based Adherence Program on Blood Pressure Control Among Hypertensive Patients - Faisal, Faisal; Anto, Ambo; Ibrahim, Muhammad Indra (Journal of Applied Nursing and Health, 2026)
Background: Hypertension is a chronic disease often referred to as a "silent killer" because it frequently presents without symptoms until serious complications occur. Adherence to blood pressure control is essential for successful management and prevention of complications. However, adherence among hypertensive patients remains low in many primary healthcare settings. To address this issue, the "Ikan Manori Sapuka" program was implemented as a community-based intervention to improve patient adherence to blood pressure control. This study aims to determine the effectiveness of the Ikan Manori Sapuka program in improving adherence among hypertensive patients. Methods: This study used a pre-experimental one-group design that followed the TREND reporting guideline. The sample consisted of 84 respondents obtained through a total sampling technique. Inclusion criteria included patients aged 40–85 years who consented to participate, while exclusion criteria were a history of stroke or refusal to participate. Data analysis was performed using the McNemar test to see significant differences before and after the intervention. Results: Adherence to blood pressure control increased from 33.3% before the intervention to 82.1% after the intervention. This improvement was statistically significant (p < 0.001), with a risk difference of 48.8%, indicating a substantial magnitude of improvement following the intervention. Conclusion: The findings demonstrate that a structured, community-based intervention significantly improves adherence to blood pressure control among hypertensive patients in remote island settings. This evidence supports the use of low-cost, locally adaptable community engagement strategies to strengthen hypertension management in primary healthcare services.